2005
DOI: 10.1002/polb.20389
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of plastic deformation in glassy polymers: Atomistic and mesoscale approaches

Abstract: The mechanism of deformation in glasses is very different from that of crystals, even though their general behavior is very similar. In this study, we investigated the deformation of polycarbonate on the atomistic scale with molecular dynamics and on the continuum scale with a new simulation approach. The results indicated that high atomic/segmental mobility and low local density enabled the formation (nucleation) of highly deformed regions that grew to form plastic defects called plastic shear transformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Many studies have focused on modeling and simulation of polymers and polymer-based nanocomposites via MM and MD techniques (Theodorou and Suter, 1986;Fan et al, 1994;Lordi and Yao, 2000;Sane et al, 2002;Frankland et al, 2003;Griebel and Hamaekers, 2004;Hu and Sinnott, 2004; 0020-7683/$ -see front matter Ó 2006 Elsevier Ltd. All rights reserved. doi:10.1016/j.ijsolstr.2006.06.011 Liang et al, 2004;Odegard et al, 2004;Odegard et al, 2005;Shenogin and Ozisik, 2005). These studies have demonstrated that molecular modeling techniques can be effectively used to predict both structure and elastic mechanical properties of polymer-based material systems.…”
Section: Introductionmentioning
confidence: 93%
“…Many studies have focused on modeling and simulation of polymers and polymer-based nanocomposites via MM and MD techniques (Theodorou and Suter, 1986;Fan et al, 1994;Lordi and Yao, 2000;Sane et al, 2002;Frankland et al, 2003;Griebel and Hamaekers, 2004;Hu and Sinnott, 2004; 0020-7683/$ -see front matter Ó 2006 Elsevier Ltd. All rights reserved. doi:10.1016/j.ijsolstr.2006.06.011 Liang et al, 2004;Odegard et al, 2004;Odegard et al, 2005;Shenogin and Ozisik, 2005). These studies have demonstrated that molecular modeling techniques can be effectively used to predict both structure and elastic mechanical properties of polymer-based material systems.…”
Section: Introductionmentioning
confidence: 93%
“…Open Babel (website: http://openbabel.org, accessed on 2 December 2022) was used to perform file conversions [36]. Two amorphous molecular structures of SOL were built by Xenoview v.3.7.9.0 (available online at www.vemmer.org/ xenoview/xenoview.html, accessed on 2 December 2022) [37].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…This is due to the breakdown of elasticity theory, which is known to be invalid near the core of a dislocation, and not a limitation of the dipole tensor approach. It is expected that with a properly computed strain field (using methods such as Falk and Langer's method 42 of using a least squares fit to the displacement to compute the deformation gradient, the Voronoi polyhedra approach of Mott et al 43 , or the least squares method used by Shenogin and Ozisik 44,45 ), the agreement of atomistics with the predicted values will be better.…”
Section: B Vacancy Energetics In the Vicinity Of An Edge Dislocationmentioning
confidence: 99%